Extending binary operations to funtor-spaces - Banakh, T.O.; Gavrylkiv, V.M. (Carpathian Mathematical Publications, 2009)
Given a continuous monadic functor T:Comp→Comp in the category of compacta and a discrete topological semigroup X we extend the semigroup operation φ:X× X→ X to a right-topological semigroup operation Φ:Tβ X× Tβ X→ Tβ X, whose topological center Λ_Φ contains the dense subsemigroup T_f X consisting of elements aTβ X that have finite support in X.